Graph theory - Aksa, Karima (2022)
Graph theory is a vast field that constitutes a very important body of knowledge. Indeed, this book is just an introduction aiming at clarifying some essential points in this vital field: basic notions, some basic algorithms that are used to solve some classical and famous problems like path finding, tree finding, flow finding, ...etc. Finally, graph theory can be summarized by what Napoleon said: "A little drawing is better than a big speech".